2006
DOI: 10.1002/ijc.21978
|View full text |Cite
|
Sign up to set email alerts
|

Folate fortification, plasma folate, homocysteine and colorectal adenoma recurrence

Abstract: In 1996, the US Food and Drug Administration mandated the fortification of grain products with folic acid, a nutrient that has been associated with lower risk of colorectal neoplasia. We assessed the relation of plasma folate and homocysteine and colorectal adenoma recurrence separately in 2 studies: the first involved an intervention of a cereal supplement that contained folic acid, wheat bran fiber (WBF), and the second was conducted primarily during postfortification of the food supply using ursodeoxycholic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 29 publications
(51 reference statements)
4
46
0
Order By: Relevance
“…We believe the effects of a chemopreventive agent, especially one based on a dietary component, may vary depending on the baseline state of sufficiency. Previous results showed that folate supplementation may protect against adenoma or cancer only in those with low baseline folate levels (30). Our data strongly support this theory; therefore, people with low plasma folate should be encouraged to take adequate folate supplements based on the potential perceived risk of CRCs.…”
Section: Discussionsupporting
confidence: 82%
“…We believe the effects of a chemopreventive agent, especially one based on a dietary component, may vary depending on the baseline state of sufficiency. Previous results showed that folate supplementation may protect against adenoma or cancer only in those with low baseline folate levels (30). Our data strongly support this theory; therefore, people with low plasma folate should be encouraged to take adequate folate supplements based on the potential perceived risk of CRCs.…”
Section: Discussionsupporting
confidence: 82%
“…Hyperhomocysteinemia, a well-known risk factor for cardiovascular diseases, can increase the production of oxygen free radicals through homocysteine oxidation and can diminish the DNA methylation in critical tissues through a simultaneous increase in intracellular S-adenosylhomocysteine and is thus a risk factor for cancer [46,47]. Although some previous studies did not show that high plasma homocysteine was significantly associated with the development of colorectal polyps [48,49], the present study, in agreement with other studies [19,20,21,22], demonstrated that an increased plasma homocysteine concentration was associated with the development of colorectal polyps. …”
Section: Discussionsupporting
confidence: 91%
“…In the last decade, much attention has also been paid to the relationship between high plasma homocysteine levels and the risk of colorectal polyps [19,20,21,22]. Besides the many known risk factors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…There was a weak inverse association between dietary folate intake and colorectal cancer risk (14), and blood folate levels were inversely associated in some (15)(16)(17)(18), but not all (10,(19)(20)(21)(22)(23)(24) studies. Vitamin B12 status was not associated with colorectal cancer in the majority of the studies (21,(24)(25)(26).…”
Section: Introductionmentioning
confidence: 98%